Efektivitas Pijat Bayi Terhadap Peningkatan Kualitas Tidur Bayi di Puskesmas Bangkala Kota Makassar: The Effectiviness Baby Massage To The Baby’s Sleeping Quality in Community Healthy Center Bangkala Makassar city - Hidayah, Nur (Jurnal Ilmiah Amanah Akademika, 2019)
Baby sleep quality was very influential in the growth and development of infants. Problems experienced by the mother is the baby that isvery difficult to sleep. One effort that can be done to help improve the quality and quantity of sleep a baby is to massage your baby, which can stimulate the release of endorphins that can reduce pain so that the baby be quiet and reduce the frequency of crying. The purpose of this study was to determine the effectiveness of infant massage on the quality of infant sleep in Community Healthy Center Bangkala Makassar city. The study design used is quasy Experimental. The independent variables were infant massage therapy, while the dependent variable is the quality of infant sleep. Samples were infants aged 3-6 months. The instrument used was an open questionnaire. Analysis of data through two stages. Phase I of the data normality test. Phase II is used Effect Test is a two-way ANOVA (two way ANOVA). There was a significant influence on the duration of sleep quality infant massage in the Community Healthy Center Bangkala Makassar city (p-value = 0.041 <0.05). There was a significant influence on the quality of sleep frekuensii massage infants in the Community Healthy Center Bangkala Makassar city (p-value = 0.005 <0.05). There was a significant interaction (significant) between the duration of time the infant massage frekuesni on the quality of infant sleep in the Community Healthy Center Bangkala Makassar city (p-value = 0.001 <0.05).